Optimization on co-composting of horse manure with pineapple waste composition using response surface methodology (RSM) - Mohd Sokri, S S; Tee, T P; Nurin, A M Y; Azhar, S; Nayan, N; Hj Suyub, I B (IOP Publishing, 2023)
Horse manure (HM) content of nitrogen and phosphorus can improve soil nutrient as organic fertilizer. Biodegradable pineapple waste (PW) contains high organic carbon, which is also a good bulking agent if appropriately treated with HM through co-composting to optimize the better quality of the co-compost product. The study objective was to optimize the composting quality of HM with PW via response surface methodology (RSM). Twenty treatments based on 3 level codes (-α, 0, +α) of three compositing factors, namely co-composting period (20, 25, 30 days), percentage of composition HM: PW (85:15, 90:10, 95:5) and particle size of PW (0.25, 0.50, 0.75 cm), respectively were designed using the central composite design (CCD). At the end of composting period, the carbon to nitrogen ratio (C/N), dry matter (DM), organic matter (OM), moisture content (MC), bulk density and pH were determined as co-compost qualities (dependent responses). The optimum results indicated that the Day 20 of composting period, composition 95:5 (HM: PW) and 0.25 cm of particle size had significant optimum values of 27.2 % DM, 72.8 % MC, 90.3 % OM and pH 6.7. No significant interaction of the three factors was found on C/N ratio and bulk density by RSM analysis. Subsequently, the significant results of optimum value developed a prediction model for co- composting HM and PW.